Reliability and Validity Test of the Indonesian Version of the Nordic Musculoskeletal Questionnaire (NMQ) to Measure Musculoskeletal Disorders (MSD) in Traditional Women Weavers - Iwan Muhamad Ramdan; Krispinus Duma; Dina Lusiana Setyowati (Universitas Islam Bandung, 2019)
Musculoskeletal disorder remains to be a health and safety problem. One of measuring instrument often use to assess musculoskeletal disorders worldwide is the Nordic musculoskeletal questionnaire (NMQ). This questionnaire translated into various languages and tested for its validity and reliability. However, it has limitations, such as the difficulty of application in countries that do not speak English. This study aims to test the validity and reliability of the Indonesian version of NMQ in women weavers working using traditional handlooms in East Kalimantan Indonesia from March to May 2018. The validity of items obtained ranges 0.501 (min.) to 0.823 (max.), and Cronbach's alpha reliability was 0.726. In conclusion, the NMQ in Indonesian version has satisfactory psychometric properties with adequate validity and reliability. UJI VALIDITAS DAN RELIABILITAS NORDIC MUSCULOSKELETAL QUESTIONNAIRE (NMQ) VERSI INDONESIA UNTUK MENGUKUR GANGGUAN MUSKULOSKELETAL PADA PENENUN TRADISIONAL WANITAGangguan muskuloskeletal masih menjadi masalah kesehatan dan keselamatan kerja. Salah satu alat ukur yang sering dipakai untuk mengkaji gangguan muskuloskeletal di seluruh dunia adalah Nordic musculoskeletal questionnaire (NMQ). Kuesioner ini telah diterjemahkan ke berbagai bahasa di dunia dan terbukti valid serta reliabel, tetapi memiliki keterbatasan di antaranya sulit diaplikasikan di negara yang tidak menggunakan bahasa Ingris sebagai bahasa sehari-hari. Penelitian ini bertujuan menguji validitas dan reliabilitas NMQ versi bahasa Indonesia pada penenun tradisional wanita di Kalimantan Timur periode Maret sampai Mei 2018. Didapatkan hasil uji validitas item berkisar antara 0,501 (min.) sampai 0,823 (maks.) dan indeks reliabilitas Cronbach's alpha sebesar 0,726. Simpulan, NMQ versi bahasa Indonesia cukup valid dan reliabel untuk mengukur gangguan muskuloskeletal.